DYNAMICS OF INTERNAL EQUILIBRIUM: EFFECTIVENESS OF CAPITAL STRUCTURE IN MODERATING COMPANY CHARACTERISTICS IN RELATION TO LQ45 INDEX VALUE - M. Imam Suswandoyo; Muh. Rays; Yohanes August Goenawan; Atika Purnamasari (Jurnal Widya Akuntansi dan Keuangan, 2026)
This study aims to examine how profitability, liquidity, and firm size influence firm value, with capital structure as a moderating variable for this relationship. The scope of this study is LQ45 companies listed on the Indonesia Stock Exchange (IDX). The data used in this study were obtained from audited financial statements in the form of secondary data and annual reports for the period 2020 to 2024. The sampling approach used a purposive sampling approach and resulted in 170 company data for a five-year period. The results show that firm value is not significantly affected by profitability. Liquidity and firm size have a significant negative effect on firm value. Capital structure cannot moderate the effect of liquidity on firm value, but it can strengthen the effect of profitability on firm value and weaken the effect of firm size on firm value. This study strengthens the understanding of signaling theory and internal corporate characteristics in the context of large companies in the LQ45 index. This study provides a new perspective that, in the context of large companies in the Indonesian capital market, the quality of the financing structure determines the strength of the signal to the market more than traditional financial characteristics.